The resistance of urban poor upon the modern medication system: Reaction towards the power domination practice of the medical regime - Septi Ariadi; Partini Partini; Mohammad Supraja (Faculty of Social and Political Science, Universitas Airlangga, 2017)
The power domination that reflected in the form of dominant discourse and normality management done by the medical regime through the hegemony process and the panoptic mechanism upon the individual and society in concrete is marked by the presence of regulation and surveillance (monitoring) in the medical fields. This study focuses the attention on the attempt in understanding and analyze the process and the resistance of urban poor upon the modern medication system that is internalized by medical regime as well as to explain the base or the potential problem that could become the trigger for the occurrence of resistance. This study also discuss the power relation that is made with the health personnel as well as to identify the base or the background that causing the resistance. This study used the qualitative-inductive method and the reflexive methodology. With the critical perspective and using the reflexive methodology from this study, conclusion can be drawn the power domination that is demonstrated by the medical regime has create the critical awareness of the urban poor that is followed by the process of resistance that is realized in the technique of low profile by avoiding, retracting, fatalist and passive. All of that is according to the characteristics of the low class structure as well as the resistance that is personal, spontaneous, and expressive; that tend to be manifested as well as exit and developed an alternative discourse/ otherness according to the autonomy of willingness and power owned by the urban poor. In the context of resistance act of urban poor is realized in three shapes: (a) urban poor developed skepticism and criticism upon the modern medication although they still accessing the modern medication, (b) developed the pluralistic-patterned medical orientation or the combinative one. Lastly, (c) the exit of urban poor and developed the alternative discourse/otherness about the medication system to gain the recovery according to the autonomy of willingness and power held by it.